Լեռնային Ղարաբաղի բարձրագույն նոր կրթական համակարգի ձևավորման ու զարգացման հիմնական ուղղությունները և նրա սերտաճումը Հայաստանի կրթական համակարգի հետ - Ավանեսյան, Արպատ; Ասրյան, Լիլիյա
В статье кратко описаны исторические периоды развития образовательной системы Арцаха с 5-ого века до наших дней, отмечены виды и функции образовательных учреждений основанных в этот период в Армении и в Арцахе в ее неотъемлемой части. В статье обсуждены процесс формирования новой школьной сети в период включения Армении и Арцаха в состав царской России, а также изменения в этой сфере осуществленные в советские годы. Кратко представлен процесс включения образовательной системы в Арцахе в результате арцахского освободительного движения. The article briefly presents the stages of historical development of educational system in Artsakh from the 5th century up to now as well as the types and functions of currently acting educational institutions that were established in Armenia and in its indivisible part Artsakh during that period. A special emphasis has been put on the formation of new educational network within the period when Armenia and Artsakh were included into Tsarist Russia, and the changes being realized in this sphere in the Soviet years. The process of integration of Artsakh educational system into Armenia‘s one as a result of Artsakh liberation movement is briefly introduced.
Keywords: Մանկավարժության տեսություն և պատմություն